Revisiting the language question in Zimbabwe: a multilingual approach to the language in education policy - Magwa, Wiseman (Routledge, 2021)
Zimbabwe is a multilingual country with a less complex multicultural society than other African nations, but the country's national language policy continues to marginalize indigenous African languages at all levels of the country's education system. The aim of this paper is to argue strongly for the recognition and use of all indigenous African languages spoken in the country in both the private and public spheres. The discussion confirms the assertion that when minority linguistic rights are acknowledged, the full participation of minority groups in all national activities is guaranteed. It is again made very clear in the debate that Zimbabwe inherited from Rhodesia a racially structured system of education in which two parallel systems existed. As a way forward, the paper proposes a language policy framework code-named ITEM (Integrated Trilingual Education Model) that could be adopted to enable the country's citizens to actively participate in national development.